Analisis Kesiapan Guru Dalam Menerapkan Kurikulum Merdeka Belajar (Studi Kasus di Sekolah Dasar Negeri 2 Batujai) - Sadli, Muhamad; Saadati, Baiq Arnika (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to describe and analyze the readiness of Batujai 2 Public Elementary School teachers in implementing the independent learning curriculum. The type of research used is descriptive qualitative research. Data collection techniques were carried out by interviewing, observing, and documenting school principals and teachers. Data were analyzed with an interactive model consisting of data reduction, data presentation, and drawing conclusions. The results of the study showed that on the whole the teachers at SDN 2 Batujai were ready to implement the independent curriculum. This can be seen from:(1) The teacher has attended the training several times. Including strengthening training from clusters and sub-districts so that teachers have a comprehensive understanding of the independent curriculum. (2) The teacher can design an independent curriculum learning implementation plan or what is called a 1 sheet RPP. (3) The learning process at SDN 2 Batujai grade 1 and grade 4 has reflected the main characteristics of the independent curriculum, namely providing teaching materials that focus on essential material (deep learning on the development of literacy and numeracy). (4) facilities and infrastructure that are fairly complete starting from the teaching materials or books used, namely using a subject approach. (5) Science and Social Studies lessons at SDN 2 Batujai have been merged into a science subject, learning English at SDN 2 Batujai has become an elective subject no longer an extracurricular subject, while teachers who teach English subjects at SDN 2 Batujai are not a class teacher but a special teacher who has qualifications in the field or department of English, the SBDP subject at SDN 2 Batujai has been changed to art education and PPKN subjects to Pancasila education. Keywords: Teacher readiness, independent curriculum